Case Report: All that glitters is not cancer; perihepatic hibernoma with fluctuating FDG uptake on PET/CT - Ramzan, Amaila; Chander, Amarjot; Westwood, Thomas; Elias, Mark; Manoharan, Prakash (Frontiers in Nuclear Medicine, 2024)
Hibernomas are rare brown fat tumors that garnered attention in the literature with the increasing use of [18F] Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography ([18F] FDG PET/CT) for the staging workup and follow-up of solid malignancies. Despite being benign tumors, they exhibit high metabolic activity due to their thermogenic nature, leading to significant radiotracer uptake on functional imaging. This can pose a challenge in differentiating them from the malignant lesions, especially the fat-containing malignancies such as liposarcoma. Hibernomas are typically found in the thigh, shoulder, back, and neck. Here, we present a unique case of Hibernoma in a patient undergoing PET/CT for melanoma follow-up in an unusual perihepatic location. To the best of the authors’ knowledge, this represents the first reported case of a perihepatic hibernoma in the literature. The report also offers a literature review on hibernomas, including the influence of ambient temperature on their metabolism, diagnostic challenges, management strategies, and reports of hibernomas detected on functional imaging with a range of radiotracers. These observations could serve as a valuable clue in identifying hibernomas, potentially aiding in avoiding unnecessary biopsies or resections.